Geoelectrical investigation for potential groundwater zones in parts of Ratnagiri and Kolhapur districts, Maharashtra - Gupta, Gautam; Erram, Vinit C.; Maiti, Saumen (My University, 2015)
Study of significant variations in nature and extent of weathering due to the presence of fractures and lineaments at depth and the geomorphological features at the surface is vital for groundwater exploration in a hard rock terrain. An attempt is made here to understand the vertical distribution of water bearing zones in the shallow formations over Devrukh-Ganapati Pule and Malkapur-Ratnagiri sections through geoelectrical studies. Two-dimensional geoelectrical cross-sections along five profiles reveal potential aquifer zones at a few sounding locations viz. 1, 2, 4, 5, 6, 7, 17, 18, 20, 21 and 22 with resistivities varying from 22-36 Ω-m over Devrukh- Ganapati Pule profile. Potential aquifer zones are also revealed at sounding points 24, 25, 34, 37, 39, 40, 41 and 42 in the eastern part of the Malkapur-Ratnagiri profile in the resistivity range of 22-37 Ω-m. Several lineaments cris-crossing this region play a significant role in the occurrence and movement of groundwater as revealed by low resistivities near VES 6, 5, 4, 16 and 17 over Devrukh-Ganapati Pule profile and VES 24, 25, 34 and 37 over Malkapur-Ratnagiri profile.
Keywords: Groundwater; Groundwater exploration; Ratnagiri; Kolhapur